Kai kurie teksto stilistinės sandaros aspektai - Buitkienė, Janina (Kalbotyra, 1997)
It is difficult to find stylistically neutral texts in any language. First of all, every text belongs to a certain functional style therefore it becomes stylistically marked. Next, every text is constructed by a speaker or writer, who, as a rule, expresses his attitude towards what is said in the text. To develop the main idea of a text and to express his evaluation of it, the author is free to choose language units of different levels: stylistic devices, means of sentence cohesion, etc. This influences not only the structure and semantics of the text but also its stylistic organisation.